Method for producing Fe-Co alloy bar

By adopting the heating straight process and omitting the solution treatment in the production process of Fe-Co alloy rods, the problem of difficulty in stably obtaining high magnetic characteristics in the prior art is solved, and better magnetic characteristics and high strength are achieved.

CN119768552APending Publication Date: 2025-04-04PROTERIAL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062130.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-02
Filing Date
2023-09-01
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The conventional Fe-Co alloy rod manufacturing method is difficult to achieve stable high magnetic characteristics, and the magnetic characteristics of the rod material omitted from solution treatment are slightly reduced, leaving room for improvement.

Method used

By adopting the heating straight process, the hot-rolled material of the Fe-Co alloy is heated at 500°C to 900°C and tensile stress is imparted, and the solution treatment is omitted to improve the magnetic characteristics of the rod.

Benefits of technology

This method can stably obtain better magnetic characteristics, with a coercive force of 42 A/m or less and a magnetic flux density (B2000) of 2.2 or more, taking into account both stable magnetic characteristics and high strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a method for producing a Fe-Co alloy bar, which is capable of stably obtaining more excellent magnetic characteristics. A method for producing an Fe-Co alloy bar, the method comprising a heating and straightening step for applying a tensile stress to a hot-rolled material of an Fe-Co alloy containing, in mass%, 95% or more of Fe + Co, 25%-60% of Co, 1.70%-2.10% of V, 0.01%-0.15% of Mn, 0.008% or less of C, 0.01% or less of S, and the balance being unavoidable impurities, while heating the hot-rolled material to 500-900 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a Fe-Co alloy bar and the Fe-Co alloy bar. Background Art

[0002] Fe-Co alloy bars represented by Permendur (hereinafter also referred to as Permendur) are used in various products such as sensors, cylindrical magnetic shields, solenoid valves, and magnetic cores due to their excellent magnetic properties. As a method for manufacturing the Fe-Co alloy bars, for example, Patent Document 1 describes the following: After heating the ingot to 1000°C to 1100°C, hot working it into a billet of about φ90 mm, removing scratches on the surface using a lathe, and hot rolling it to about φ6 mm to φ9 mm after heating it to 1000°C to 1100°C, thereby manufacturing the raw material (bar).

[0003] In addition, the applicant of the present application proposed a Fe-Co alloy rod and a method for manufacturing the Fe-Co alloy rod in Patent Document 2, wherein the Fe-Co alloy rod can stably obtain excellent magnetic properties and has more than 20% of grains with a grain orientation spread (GOS) value of more than 0.5° in terms of area ratio, and the method for manufacturing the Fe-Co alloy rod includes a heating straightening process of heating the hot-rolled material to a temperature of 500°C to 900°C while applying tensile stress.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Laid-Open No. 7-166239

[0007] Patent Document 2: International Publication No. 2021 / 182518 Summary of the invention

[0008] Problems to be solved by the invention

[0009] As the products become more high-performance, the raw materials are also required to further improve their magnetic properties. In the previous manufacturing method as described in Patent Document 1, it is difficult to stably obtain high magnetic properties, leaving room for further research. The Fe-Co alloy rod described in Patent Document 2 has excellent magnetic properties and is a very useful invention. On the other hand, the strength of the rod that omits the solid solution treatment is excellent, but sometimes the magnetic properties are slightly lower than those of the rod that has been subjected to the solid solution treatment, leaving room for improvement. Therefore, the purpose of the present invention is to provide a method for manufacturing a Fe-Co alloy rod that can stably obtain better magnetic properties.

[0010] Technical means of solving problems

[0011] The present invention has been made in view of the above-mentioned problems.

[0012] That is, one embodiment of the present invention is a method for manufacturing an Fe-Co alloy rod, comprising a heating straightening step, wherein the heating straightening step applies tensile stress to a hot-rolled material of the Fe-Co alloy while heating the hot-rolled material to a temperature of 500°C to 900°C, wherein the hot-rolled material of the Fe-Co alloy contains, by mass%, Fe+Co: 95% or more, Co: 25% to 60%, V: 1.70% to 2.10%, Mn: 0.01% to 0.15%, C: 0.008% or less, S: 0.01% or less, and the remainder being unavoidable impurities.

[0013] It is preferred not to perform a solution treatment before performing the heating and straightening step.

[0014] Effects of the Invention

[0015] According to the present invention, it is possible to obtain a Fe—Co alloy rod material capable of stably obtaining more excellent magnetic properties. DETAILED DESCRIPTION

[0016] The following is an explanation of the embodiments of the present invention. First, the method for manufacturing the Fe-Co alloy rod of the present invention is explained. The Fe-Co alloy rod of the present invention is a straight rod having a circular (including elliptical) or square cross-sectional shape. The rod of the present embodiment is a round rod having a circular cross-sectional shape unless otherwise specified.

[0017] <Hot-rolled material composition>

[0018] First, the reasons for limiting the composition of the Fe—Co alloy specified in the present invention will be described.

[0019] Fe+Co: 95 mass % (hereinafter also simply expressed as %) or more, Co: 25% to 60%

[0020] In the present invention, an Fe-Co alloy is used in which Fe+Co is 95% or more and Co is 25% to 60%. The preferred lower limit of Co is 40%. Thus, high magnetic flux density and high magnetic permeability can be exerted. In addition, the preferred content of Fe+Co is 97% or more.

[0021] V: 1.70%~2.10%

[0022] If V is too little, it will cause embrittlement and reduce the workability in the subsequent process, so it is contained in the present invention at 1.70% or more. On the other hand, if the amount of V is too much, in addition to reducing the magnetic flux density, a large amount of fine V-based carbides are dispersed in the matrix, causing the excitation characteristics and iron loss characteristics to decrease, so it is added in mass % or less 2.10%. The preferred upper limit of V is 2.00%. In addition, in order to further improve the magnetic properties, the preferred upper limit of V is 1.95%.

[0023] Mn: 0.01%~0.15%

[0024] Mn fixes the impurity element S to MnS through its addition, so it has an effect on improving the excitation characteristics and iron loss characteristics, but if it is too much, it will cause a decrease in the excitation characteristics and iron loss characteristics. In particular, excessive addition of Mn becomes a factor that reduces the precipitation temperature of the γ phase during magnetic annealing, so in the present invention, 0.01% to 0.15% or less is added. The preferred upper limit of Mn is 0.10%.

[0025] C: 0.008% or less, S: 0.01% or less

[0026] C and S are impurity elements that hinder good excitation characteristics and iron loss characteristics. If more than 0.005% of C or more than 0.01% of S remain, good excitation characteristics and iron loss characteristics cannot be stably obtained. Therefore, in the present invention, C and S are limited to C: less than 0.008% and S: less than 0.01%. The preferred upper limit of C is 0.005%, and the preferred upper limit of S is 0.005%. In addition, as impurity elements that are inevitably included, for example, Si, P, and O can be listed, and it is preferred that the upper limit of each of the elements is set to 0.1%, for example.

[0027] In the Fe-Co alloy of the present invention, the V and Mn that are actively added are preferably set to a total amount of 2.1% or less on the basis of satisfying the above range. As a result, there is a tendency to suppress excessive coercive force and stably obtain good excitation characteristics and iron loss characteristics. In addition, as mentioned above, Mn fixes the impurity element S to MnS through its addition. Therefore, in order to obtain the effect of more reliably fixing the impurity S, it is preferred to set Mn:S to a range of 10 to 100.

[0028] In this embodiment, as an intermediate raw material of the Fe-Co alloy bar, a billet obtained from the Fe-Co alloy steel block having the above composition is hot rolled to obtain a hot rolled material. Since an oxide layer is formed on the intermediate raw material by hot rolling, a grinding process for removing the oxide layer mechanically or chemically may be introduced.

[0029] The hot-rolled material has, for example, a shape of a "hot-rolled bar" equivalent to a Fe-Co alloy bar. In addition, in consideration of workability in subsequent steps, the diameter may be set to 5 mm to 20 mm. In addition, for bars other than round bars, the circle equivalent diameter of the cross section may also be set to 5 mm to 20 mm.

[0030] <Solution treatment process>

[0031] In the present embodiment, for the hot-rolled material before the heating straightening process described later, at least one solid solution treatment can be performed. By performing the solid solution treatment, it is also expected to remove the component segregation of the hot-rolled material and improve the magnetic properties, thereby improving the effect of processability. If the heating temperature during the solid solution treatment is too low, there is a tendency to deteriorate the processability, and if it is too high, it leads to the deterioration of the magnetic properties, so it is preferably implemented at a temperature of 800°C to 1050°C. The more preferred lower limit of the temperature is 850°C. The more preferred upper limit of the temperature is 950°C, and the more preferred upper limit of the temperature is 900°C. In addition, the heating time can also be set to 10 minutes to 60 minutes. In addition, in the solid solution treatment process, in order to dissolve without precipitating harmful precipitates, inhibit ordering and improve processability, a quenching treatment is performed after heating.

[0032] In addition, even if the solution treatment process is omitted, the effect of the present invention can be obtained by adjusting the heating temperature of the heating straightening process described later. It is preferred to omit (not implement) the solution treatment process. The Fe-Co alloy composition in the present embodiment has excellent magnetic properties. On the other hand, compared with the previous Fe-Co alloy, the grains tend to become coarse, resulting in a deviation in the strain applied to the material during the heating straightening process, which may become a factor that makes the magnetic properties unstable. By omitting the solution treatment process, the structure of the hot-rolled material can be made into a uniform and fine rolling structure with little deviation in the strain in the heating straightening process, and the formation of coarse grains in the Fe-Co alloy bar after magnetic annealing is suppressed, and the coercive force is stably equal to or higher than that of the previous solution treatment product, and the mechanical strength is also improved.

[0033] <Heating and straightening process>

[0034] In this embodiment, for the hot-rolled material, a heating straightening process of imparting tensile stress while heating is performed. At this time, if the hot-rolled material is in the shape of a "bar", it is stretched along the length direction of the hot-rolled bar to impart the tensile stress. Through the process, a bar having very good magnetic properties and straightness can be obtained while imparting residual strain to the hot-rolled material. The heating temperature at this time is set to 500°C to 900°C. When it is lower than 500°C, the workability is reduced, and the bar may break when imparting tensile stress. On the other hand, when the heating temperature exceeds 900°C, the hot-rolled material cannot be given a preferred residual strain. The lower limit of the preferred heating temperature in the heating straightening process is 600°C, and more preferably 700°C. In addition, the upper limit of the preferred heating temperature is 850°C, more preferably 830°C, and more preferably 800°C. In addition, when the solution treatment process is omitted, the lower limit of the preferred heating temperature is 700°C, more preferably 730°C, and more preferably 740°C.

[0035] In the heating straightening process, heating methods such as energizing heating and induction heating can be used. In terms of the effect of easily aligning the easy magnetization axis of the grains in the hot-rolled material in a certain direction and the advantage of being able to quickly (for example, within 1 minute) and uniformly heat the material to the target temperature, it is preferred to apply energizing heating. In addition, in order to more reliably obtain the required residual strain, the tensile load applied to the bar during the heating straightening process is preferably adjusted to 4 kN to 90 kN. In addition, it is preferably adjusted to an elongation of 3% to 10% relative to the total length before the heating straightening process.

[0036] In this embodiment, the bar material that has completed the heat straightening process can also be subjected to centerless grinding using a centerless grinder, for example. This can remove the black skin on the surface of the bar material, and further improve the roundness or tolerance accuracy of the shape. In the present invention, since the straightness of the bar material is improved by the heat straightening process, a long bar material with a length of more than 1000 mm can also be subjected to centerless grinding without cutting.

[0037] The Fe-Co alloy rod obtained by the manufacturing method of the present invention has excellent magnetic properties (for example, the coercive force is 42 A / m or less, and the magnetic flux density (B2000) under the applied magnetic field of 2000 A / m is 2.2 or more). Here, in the case of taking into account both stable magnetic properties and high strength, it is preferred to omit the solid solution treatment process, and in the case of further improving the magnetic properties, solid solution treatment can also be performed. In the case of omitting the solid solution treatment, the coercive force can be set to 42 A / m or less, and the 0.2% proof strength after magnetic annealing can be set to 200 MPa or more. The more preferred 0.2% proof strength is 210 MPa or more. The 0.2% proof strength can be measured based on the metal material tensile test method of Japanese Industrial Standards (JIS) Z2241. In the case of implementing solid solution treatment, the coercive force can be set to 35 A / m or less. The grain size number of the Fe-Co alloy rod obtained by the manufacturing method of the present invention is preferably 5.0 or more and 11.0 or less. Thus, it is easy to exert high magnetic properties after magnetic annealing. In the case of omitting the solution treatment process, in order to take into account both stable magnetic properties and high strength, the preferred crystal grain size numbering lower limit of the Fe-Co alloy bar is 7.0, and the preferred crystal grain size numbering upper limit is 10.5. The preferred crystal grain size numbering lower limit is 7.5, and the preferred crystal grain size numbering upper limit is 10.0. In the case of implementing solution treatment, in order to further improve magnetic properties, the preferred crystal grain size numbering lower limit is 5.5, and the preferred crystal grain size numbering upper limit is 7.0. In addition, the crystal grain size numbering can be measured based on JIS G0551. And, it can be measured in the right angle section or axial section of the bar.

[0038] Example

[0039] (Example 1)

[0040] An Fe-Co alloy steel ingot having the composition shown in Table 1 was divided into blocks and then hot-rolled to prepare hot-rolled bars of φ11.5 mm.

[0041] <No.1、No.11>

[0042] After the hot-rolled bar was subjected to a solution treatment of heating at 850°C and then quenching, a heating straightening process was performed in which the hot-rolled bar was stretched in its longitudinal direction under a tensile load of 27 kN while being heated so that the temperature of the bar reached 750°C, thereby producing Fe-Co alloy bars of sample No. 1 as an example of the present invention and sample No. 2 as a comparative example. In addition, the total amount of inevitable impurities was approximately 0.1% or less.

[0043] <Sample No. 2, Sample No. 12>

[0044] The hot rolled bar was subjected to a heating straightening process without solution treatment, thereby producing Fe-Co alloy bars of Sample No. 2 as an example of the present invention and Sample No. 12 as a comparative example. The conditions of the heating straightening process were the same as those of Sample No. 1. In addition, the total amount of unavoidable impurities was approximately 0.1% or less.

[0045] [Table 1]

[0046]

[0047] Then, the grain size number, DC magnetic properties and 0.2% yield strength of the samples of the present invention and the comparative example were confirmed. Regarding the average grain size, in the cross section (section in the direction perpendicular to the axis), an optical microscope manufactured by Olympus was used to observe ten fields of view of 500 μm×350 μm, and the grain size number was determined using the grain size standard plate I according to JIS G0551. Regarding the sample, the longitudinal section (axial section passing through the center axis) of the sample was observed. Regarding the DC magnetic properties, after collecting the sample from the obtained rod, a magnetic annealing of 850°C×3 hours was performed, and the coercive force was measured using a DC magnetization specific test device. In the present invention example, in addition to the coercive force, the magnetic flux density (B2000) under an applied magnetic field of 2000A / m was also measured. The 0.2% proof stress at room temperature was measured using a material having a half ratio of a JIS No. 4 test piece specified in JIS Z2241, and the 0.2% proof stress was measured based on the metal material tensile test method of JIS Z2241. Table 2 shows the results of the observation.

[0048] [Table 2]

[0049]

[0050] According to Table 2, the grain size number of sample No. 1 as an example of the present invention, which has been subjected to a solid solution treatment, is the smallest and is less than 6.5 (the grain size is the largest), and the coercive force is also less than 33 A / m, showing an excellent value, and the magnetic flux density (B2000) is also more than 2.20 T, which can also reproduce the high magnetic flux density of the Perminde alloy, so it can be confirmed that it has excellent magnetic properties. Even in sample No. 2 as an example of the present invention, which has omitted the solid solution treatment, the grain size number is 8.0, the coercive force is also less than 38 A / m, which is lower than the coercive force of sample No. 11 as a comparative example, which has been subjected to a solid solution treatment, and the magnetic flux density is also at the same level as sample No. 1 (more than 2.20 T), and the 0.2% proof strength is also more than 200 MPa and the highest among the four samples, so it can be confirmed that both good magnetic properties and high strength are achieved.

[0051] (Example 2)

[0052] Ten samples were prepared respectively, each of which was subjected to solution treatment under the same manufacturing conditions as Sample No. 1 of Example 1, and ten samples were prepared under the same manufacturing conditions as Sample No. 2 of Example 1 without solution treatment. After the samples were collected, magnetic annealing was performed at 850°C for 3 hours, and the coercive force was measured using a DC magnetization test device. When the samples with a coercive force of 42 A / m or less were considered qualified, 5 of the 10 samples that had been subjected to solution treatment were judged as qualified, while all of the 10 samples that had not been subjected to solution treatment were judged as qualified. Therefore, it can be seen that the samples that omitted the solution treatment can stably exhibit good magnetic properties.

Claims

1. A method for producing a Fe-Co alloy rod, comprising a heating straightening step of applying tensile stress to a hot-rolled material of the Fe-Co alloy while heating the hot-rolled material to a temperature of 500° C. to 900° C., The hot-rolled material of the Fe-Co alloy contains, by mass%, Fe+Co: 95% or more, Co: 25% to 60%, V: 1.70% to 2.10%, Mn: 0.01% to 0.15%, C: 0.008% or less, S: 0.01% or less, and the remainder is inevitable impurities.

2. The method for producing a Fe-Co alloy rod according to claim 1, wherein: No solution treatment is performed before performing the heating straightening step.

Citation Information

Patent Citations

  • Production of wire rod of fe-co-v alloy

    JP1995166239A

  • METHOD FOR MANUFACTURING Fe-Co-BASED ALLOY ROD, AND Fe-Co-BASED ALLOY ROD

    WO2021182518A1